101 Beyond conversational skills: novel educational approaches to promote psychological safety for clinical staff. (23rd February 2023) - Drake, Gareth; Broughton, Emma; Kerr-Elliot, Tara
Abstract : Background: The emotional impact of frontline work on nursing and medical staff has been historically neglected. It is becoming increasingly difficult to ignore this unmet need. Aims: Within the existing framework of conversation-based simulations, the GOSH Simulation Team have been working to cultivate pedagogical settings in which staff can discuss the emotional challenges of their work in ways that feel beneficial and acceptable. Methods: Theory-driven techniques have been used to give as much priority to the way in which teaching is delivered as to the content of the teaching. This has involved multi-disciplinary liaison, close attention to the learning environment, the co-creation of sessions with ward staff, bespoke scenario design, and an emphasis on sensitively facilitated reflective discussion. Results: Barriers to engagement have ranged from the linguistic: 'wellbeing', 'psychology' and 'mental health' can all come with negative associations for staff – to the practical: simply finding a suitable setting within the hospital can be difficult. Overcoming these barriers has involved close liaison with ward staff, and consultation to ensure advertising materials speak to the specific needs of learners. Simulation-based courses that have utilised the above approach have received excellent feedback. Staff attending Navigating Uncertainty in Healthcare Robin & Fox Study days Patient Safety Interview Training have reported significant increases in confidence and a positive impact on morale, as well as high clinical applicability due to learner-led discussion and bespoke scenario design. Ongoing challenges Reaching senior medical staff Embedding ongoing reflective case discussion within practice Conclusions: There is growing interest in training sessions that can speak to the often unacknowledged relational and emotional challenges that face clinical staff. The GOSH Simulation Team are attempting via the above methods to engage staff in this area in a way that feels psychologically safe and clinically useful.